Upaya Rekonsiliasi Antara BNKP Jemaat Kasih Karunia dan BNKP Jemaat Hilifalagotano Dengan Metode Appreciative Inquiry - Danezisokhi Laia; Alfons Seran (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the impact of the split and identify reconciliation efforts between the BNKP Jemaat Kasih Karunia and the BNKP Jemaat Hilifalagötanö in Tetegawa’ai Village, Mazo District, South Nias, using the Appreciative Inquiry (AI) method. The conflict between the two congregations began with differences of opinion regarding church construction and the selection of pastors, which led to the separation of the congregations in 2014. This study uses a mixed method approach, combining qualitative analysis through in-depth interviews with BPMJ, SNK, and the Head of the Commission, and quantitative analysis through questionnaires to 36 respondents. The results show that the majority of the congregations understand reconciliation as a process of restoring broken relationships, emphasizing values ​​such as making peace, forgiveness, brotherhood, as well as friendly, caring, and empathetic attitudes. Respondents consider reconciliation efforts very necessary, including through mediation, cooperation between congregations, and the wise involvement of leaders and government officials. Qualitative findings strengthen the quantitative results by confirming that appreciation for positive values, open dialogue, and active collaboration are key factors in the reconciliation process. This research confirms that the Appreciative Inquiry method is effective in rebuilding congregational harmony, strengthening fellowship, and providing a practical model for other church communities in managing similar conflicts.